Charge Transport through Self‐Assembled Monolayers of Monoterpenoids. (8th May 2019) - Cafferty, Brian J.; Yuan, Li; Baghbanzadeh, Mostafa; Rappoport, Dmitrij; Beyzavi, M. Hassan; Whitesides, George M.
Abstract: The nature of the processes at the origin of life that selected specific classes of molecules for broad incorporation into cells is controversial. Among those classes selected were polyisoprenoids and their derivatives. This paper tests the hypothesis that polyisoprenoids were early contributors to membranes in part because they (or their derivatives) could facilitate charge transport by quantum tunneling. It measures charge transport across self‐assembled monolayers (SAMs) of carboxyl‐terminated monoterpenoids (O2 C(C9 HX)) and alkanoates (O2 C(C7 HX)) with different degrees of unsaturation, supported on silver (Ag TS ) bottom electrodes, with Ga2 O3 /EGaIn top electrodes. Measurements of current density of SAMs of linear length‐matched hydrocarbons—both saturated and unsaturated—show that completely unsaturated molecules transport charge faster than those that are completely saturated by approximately a factor of ten. This increase in relative rates of charge transport correlates with the number of carbon–carbon double bonds, but not with the extent of conjugation. These results suggest that polyisoprenoids—even fully unsaturated—are not sufficiently good tunneling conductors for their conductivity to have favored them as building blocks in the prebiotic world. Abstract : Messungen des Ladungstransports durch Monolagen von Carboxy‐terminierten Monoterpenoiden mit unterschiedlichem Sättigungsgrad (von vollständig gesättigt bis vollständig ungesättigt) zeigen, dass ein Anstieg der Ungesättigtheit mit einem kleinen, aber signifikanten Anstieg der Geschwindigkeit des Elektronentunnelns korreliert. Diese Studie evaluiert auch die Hypothese, dass Terpene bei der Entstehung des Lebens für ihre Fähigkeit zum Ladungstransport selektiert wurden.